Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3233/jpd-223368
|View full text |Cite
|
Sign up to set email alerts
|

The Sequence Effect Worsens Over Time in Parkinson’s Disease and Responds to Open and Closed-Loop Subthalamic Nucleus Deep Brain Stimulation

Abstract: Background: The sequence effect is the progressive deterioration in speech, limb movement, and gait that leads to an inability to communicate, manipulate objects, or walk without freezing of gait. Many studies have demonstrated a lack of improvement of the sequence effect from dopaminergic medication, however few studies have studied the metric over time or investigated the effect of open-loop deep brain stimulation in people with Parkinson’s disease (PD). Objective: To investigate whether the sequence effect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…On the neural level, for instance, it has been shown that STN‐DBS can induce LTP‐like plasticity (Milosevic et al, 2018) and reshape and stabilize motor networks, as measured by fMRI, bringing them closer to the healthy state (Chu et al, 2023). On the behavioural level, it was found that STN‐DBS can restore motor learning that is lost in the absence of stimulation (De Almeida Marcelino et al, 2019) and counteract the sequence effect or decrement in amplitude and velocity (Kehnemouyi et al, 2023).…”
Section: Neural Reinforcement As a Target For Adaptive Deep Brain Sti...mentioning
confidence: 99%
“…On the neural level, for instance, it has been shown that STN‐DBS can induce LTP‐like plasticity (Milosevic et al, 2018) and reshape and stabilize motor networks, as measured by fMRI, bringing them closer to the healthy state (Chu et al, 2023). On the behavioural level, it was found that STN‐DBS can restore motor learning that is lost in the absence of stimulation (De Almeida Marcelino et al, 2019) and counteract the sequence effect or decrement in amplitude and velocity (Kehnemouyi et al, 2023).…”
Section: Neural Reinforcement As a Target For Adaptive Deep Brain Sti...mentioning
confidence: 99%
“…While no scientific study has addressed this hypothesis specifically, some findings can corroborate this idea. On the neural level, for instance, it has been shown that STN-DBS can induce LTP-like plasticity (Milosevic et al, 2018) and on the behavioral level it was found that it can restore motor learning that is lost in the absence of stimulation (De Almeida Marcelino et al, 2019) and it can counteract the sequence effect or decrement in amplitude and velocity (Kehnemouyi et al, 2023).…”
Section: Neural Reinforcement As a Target For Adaptive Deep Brain Sti...mentioning
confidence: 99%